ANALISIS KINERJA ORGANISASI BIDANG PASAR DINAS KOPERASI, UMKM, PERDAGANGAN, DAN PERINDUSTRIAN KABUPATEN SEMARANG - Firul Norma Riyanti; Sundarso Sundarso; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Performance is the result of work that had attained by person in a group or organization in accordance with the authority and responsibilities. Organizational performance is the achievement of result at the organizational level or unit of analysis. Performance on the level of the Organizatinal related the objectives of the Organizational, design, organization, and management of the organization. Bidang Pasar Dinas Koperasi, UMKM, Perdagangan, dan Perindustrian Kabupaten Semarang which has a role as provider of public services, especially in the field of Stup and management of Traditional market, serve the community by providing a safe market, comfortable, orderly, clean, and healthy. The purpose the research was to analyze the performance of the Bidang Pasar Dinas Koperasi, UMKM, Perdagangan, dan Perindustrian Kabupaten Semarang. Analyzing the factors that support and hinder the performance viewa of three dimensions such as responsivity, outcome, and benefit and three factors that influence the organizational such as leadership, team work, and human resources. The results of the study as a whole, the performance of the Organizatinal could not be said to be optimal. On dimensions responsivity, outcomes, team work, and human resources proved still need any improvement.